2013
DOI: 10.1111/jnc.12297
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phospho‐Ca2+/calmodulin‐dependent protein kinase II in the pre‐Bötzinger complex of rats

Abstract: The pre-B€ otzinger complex (pre-B€ otC) in the ventrolateral medulla oblongata is a presumed kernel of respiratory rhythmogenesis. Ca 2+ -activated non-selective cationic current is an essential cellular mechanism for shaping inspiratory drive potentials. Ca 2+ /calmodulin-dependent protein kinase II (CaM-KII), an ideal 'interpreter' of diverse Ca 2+ signals, is highly expressed in neurons in mediating various physiological processes. Yet, less is known about CaMKII activity in the pre-B€ otC. Using neurokini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In the current study, we investigated the effectiveness of a novel approach on the localization of low-level Pb in cultured cells at ultrastructural level. Based on our previous experiences in carrying out immunogold staining techniques for cell samples (Song et al 2014;Kang et al 2013), we designed this simple and efficient pre-embedding AMG method that does not require special devices or freezing techniques. In the present study, we found that Pb mainly accumulated in the nucleus of the established choroidal epithelial cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we investigated the effectiveness of a novel approach on the localization of low-level Pb in cultured cells at ultrastructural level. Based on our previous experiences in carrying out immunogold staining techniques for cell samples (Song et al 2014;Kang et al 2013), we designed this simple and efficient pre-embedding AMG method that does not require special devices or freezing techniques. In the present study, we found that Pb mainly accumulated in the nucleus of the established choroidal epithelial cell line.…”
Section: Discussionmentioning
confidence: 99%
“… 2014 ; Kang et al . 2013 ), we designed this simple and efficient pre-embedding AMG method that does not require special devices or freezing techniques. In the present study, we found that Pb mainly accumulated in the nucleus of the established choroidal epithelial cell line.…”
Section: Discussionmentioning
confidence: 99%
“…However, these models still lack a functional-anatomical correlation of the included neurons, the actual synaptic connections between them, as well as the distinctive morphological features of the respiratory neurons in the preBötC. Several of these molecular markers have been indeed located in the preBötC but also in other respiratory-related circuits throughout the brainstem (Gray et al, 1999(Gray et al, , 2001(Gray et al, , 2010Guyenet et al, 2002;Kang et al, 2013;Liu and Wong-Riley, 2013;Stornetta et al 2003;Tan et al, 2012). Several of these molecular markers have been indeed located in the preBötC but also in other respiratory-related circuits throughout the brainstem (Gray et al, 1999(Gray et al, , 2001(Gray et al, , 2010Guyenet et al, 2002;Kang et al, 2013;Liu and Wong-Riley, 2013;Stornetta et al 2003;Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%